Fluorescent Noble Metal Nanoclusters Loaded Protein Hydrogel Exhibiting Anti‐Biofouling and Self‐Healing Properties for Electrochemiluminescence Biosensing Applications. Issue 45 (20th October 2020) - Han, Cuiyan; Guo, Weiwei
Abstract: Electrochemiluminescence (ECL) showed great potential in various analytical applications, especially in the sensing of biotargets, taking advantage of its high sensitivity, selectivity, ease of spatial and temporal control, and simplified optical setup. However, during the sensing of complex biological samples, ECL sensors often suffered severe interferences from unavoidable nonspecific‐binding of biomacromolecules and physical damages of ECL sensing interfaces. Herein, a hydrogel based ECL biosensing system exhibiting excellent anti‐biofouling and self‐healing properties is developed. A protein hydrogel composed of bovine serum albumin (BSA) directed fluorescent Au/Ag alloy nanoclusters (Au/Ag NCs) is applied in building ECL sensing systems. The hydrogel matrix facilitates the immobilization of fluorescent Au/Ag NCs as excellent ECL probes, and the porous hydrophilic structure allows the free diffusion of small molecular biotargets while rejecting macromolecular interferences. Moreover, the hydrogel exhibits excellent self‐healing property, with the ECL intensity recovered rapidly in 10 min after cutting. The hydrogel ECL system is successfully applied in sensing glutathione (GSH) in serum, confirming the applicability of the hydrogel based anti‐biofouling ECL sensing system in sensing complex biological samples. This research may inspire the development of novel anti‐biofouling and self‐healing ECL biosensors for biosensing applications. Abstract : A protein hydrogel containing fluorescent noble metal nanoclusters is applied in electrochemiluminescence (ECL) biosensing. The hydrogel matrix is beneficial to the immobilization of Au/Ag NCs as ECL probes, and the porous hydrophilic structure facilitate the diffusion of the small molecular biotargets to the sensing interface while rejecting macromolecular interferences especially proteins. Moreover, the hydrogel ECL system exhibits excellent self‐healing property.